Armed State Building : Confronting State Failure, 1898-2012 - Miller, Paul D. (Book collections on Project MUSE., 2013)
"Since 1898, the United States and the United Nations have deployed military force more than three dozen times in attempts to rebuild failed states. Currently there are more state-building campaigns in progress than at any time in the past century--including Afghanistan, Bosnia, Kosovo, the Democratic Republic of Congo, Haiti, Sudan, Liberia, Cote d'Ivoire, and Lebanon--and the number of candidate nations for such campaigns in the future is substantial. Even with a broad definition of success, earlier campaigns failed more than half the time. In this book, Paul D. Miller brings his decade in the U.S. military, intelligence community, and policy worlds to bear on the question of what causes armed, international state-building campaigns by liberal powers to succeed or fail"--